Visual diary as a tool for idea generation for graphic design study program / Jacqueline Sim Fei Chin - Jacqueline Sim , Fei Chin (2020)
This research is to explore visual diary as a tool that allows students to express their multiple creative views and their abilities in generating ideas. This tool has been integrated as part of the selected students’ assignments and projects as a practice in the creative arts education. Many of them were taught to sketch, doodle and experiment in different drawing techniques. Nonetheless, many of them are facing the problem of lack of knowledge and understanding in the ideation process. The quantitative research design and procedures were employed in this study. A total of 35 visual diaries were selected, one each from a pool of 35 students in the graphic design program. The samples in this study were 35 (N=35) students who were enrolled to pursue the visual communication module in the first year of the graphic design program. The research was conducted at the researcher’s university, being a private institution located in Kuala Lumpur. The main tool for data collection was an assessment rubric, namely, the Ideo assessment. The quantitative data from the Ideo assessment was analysed using descriptive statistics. From the findings, it can be concluded that through the visual diary, students have shown greater understanding in the design process and that continued efforts should be made to improve, develop, and explore ideas in using the visual diary as an instructional tool for the students’ assignments and projects.